2019
DOI: 10.1155/2019/5054395
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale Roscoe) in the Prevention of Ageing and Degenerative Diseases: Review of Current Evidence

Abstract: Currently, the age of the population is increasing as a result of increased life expectancy. Ageing is defined as the progressive loss of physiological integrity, which can be characterized by functional impairment and high vulnerability to various types of diseases, such as diabetes, hypertension, Alzheimer’s disease (AD), Parkinson’s disease (PD), and atherosclerosis. Numerous studies have reported that the presence of oxidative stress and inflammation contributes to the development of these diseases. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 104 publications
2
63
0
Order By: Relevance
“…Furthermore, powder of ginger can decrease the level of glucose and activate inflammatory activity which can lead to the development of insulin resistance [ 176 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…Furthermore, powder of ginger can decrease the level of glucose and activate inflammatory activity which can lead to the development of insulin resistance [ 176 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…Our results showed that ZO extract given in combination with the obesogenic diet led to a significant reduction of damage in the peripheral blood and liver ( Figure 6). Ginger consists of two major active components, 6gingerol and 6-shogaol, which are essential for preventing oxidative stress and inflammation (78) . These bioactive compounds are able to reduce oxidative stress levels and the intake of ZO extract can therefore induce antigenotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger ( Zingiber officinale Roscoe, Zingiberaceae) has been used for thousands of years as a spice, and it has been considered to be an important ingredient in traditional Chinese medicine for the treatment of certain diseases, such as diabetes, cardiovascular diseases, rheumatism, and cancer [1,2,3,4,5,6,7,8]. In the last decade, there has also been progress in the study of other biological properties of ginger, such as its antifungal and antimicrobial capacity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gingerols and shogaols are groups of volatile phenolic compounds, and they are mainly responsible for the pungency of the rhizome [11]. It has been reported that 6-shogaol has better biological activities than 6-gingerol, especially in relation to antitumor activity [8,12].…”
Section: Introductionmentioning
confidence: 99%